Work–health–personal life conflicts in naive patients with chronic hepatitis B receiving initial treatment in China: a qualitative study. Issue 9 (14th September 2020) - Zheng, Yingjing; Zhu, Lin; Patrick, Donald; Li, Ying; Xu, Fengjiao; Zhang, Li; Song, Mengna; Cheng, Xiao; Chen, Boyan; Chen, Ying; Lu, Xiaoyang; Wang, Hongmei
Abstract : Objectives: People with chronic hepatitis B (CHB) perform sick roles, work roles and personal roles simultaneously. At times, role conflicts arise because of failure to meet the expectations of different roles. Role conflicts may increase dissatisfaction in work and family and impair their physical and mental health. This study aimed to explore the perceptions of role conflicts of treatment-naive patients with CHB in work, personal and sick roles, together with ameliorating factors in the Chinese cultural context. Design: A qualitative descriptive study. Semistructured interviews were used to collect the experience of work–health–personal life conflicts (WHPLCs), and a brief questionnaire was used to collect demographic and clinical information. SPSS V.21.0 was used for descriptive analysis and Dedoose (V.7.5.9) was used to code and analyse interview transcripts. This study selected six cities with different socioeconomic levels in Zhejiang Province, China. Then, researchers chose one tertiary hospital from each city as the study site, so a total of six tertiary hospitals were involved. Participants: We recruited 32 patients with CHB (59.38% male) who had just started antiviral therapy for no more than three months. Participants were within the age range of 19-57 years, and the average age was 36.03 (SD=9.56) years. Results: Participants noted that having CHB influenced their daily life and intersected with work and personal roles, therefore causing role conflicts. Role conflicts focused on three types: time-based conflicts, strain-based conflicts and behaviour-based conflicts. The contextual factors contributing to role conflicts were identified, including personal characteristics, financial strain, traditional social roles and work environment. Conclusions: These findings enhance our understanding of the WHPLCs experience of treatment-naive patients with CHB in China. Our findings suggest that multidimensional role conflicts should be taken into account in the intervention design and psychological counselling to improve role balance and well-being among patients with CHB.